Pendidikan Politik Islam Kepada Kaula Muda Sebagai Upaya Untuk Membentuk Kesadaran Terhadap Agama Islam - Butsainah Butsainah; Ida Inayatus Saadah; Nina Latipah Nur; Shalimar Azzahra; Salma Ramadhani Putri; Hisny Fajrussalam (AR-RASYID : Jurnal Pendidikan Agama Islam, 2022)
Islam is a very universal religion in which Islam carries the mission of rahmatan lil'alamin and brings concepts to humans regarding problems related to a system such as the concept of politics, economy, education and others. Islamic politics is the face of Islam with power and the state that can give birth to political attitudes and behavior as well as a political culture that focuses on Islamic values that focus on attitudes and behavior as well as a culture that uses Islamic adjectives. Islam lays it down as a way of looking after affairs (ri'ayah syu-un al-ummah). Where Islam and politics cannot be separated because Islam without politics will liberate Muslims who are not free and free in carrying out Islamic law. Likewise, politics without Islam will only give birth to a society that glorifies power, position and the worldly. Politics is very important for Muslims, especially young people, namely students who are the future generation of the nation and state must understand Islam both in terms of spirituality and in terms of siyahsiyah (politics). This study uses an approach with a descriptive type of study. Data collection techniques by filling out questionnaires or questionnaires and literature study. The questionnaires were filled out by a number of youths. The results of the study show that there are still many youths who are less literate in the development of Islamic politics and have not implemented it in their daily life. So it is necessary to direct and understand young people through Islamic political education to increase their awareness of the importance of Islamic politics, and can implement it in life.